A Bibliography of Canadian Imprints, 1751-1800 - Tremaine, Marie, 1902-1984 (Book collections on Project MUSE., 1999)
Marie Tremaine's bibliography was first published by UTP in 1951 and is a cornerstone of bibliography and book history studies in Canada.